Urbanization effects on hotel performance: A case study in China - Jian Ming Luo; Chi Fung Lam (Cogent Business & Management, 2017)
This paper studied the impacts of urbanization regarding the performance of hotel in Guangdong through the study of panel data from 1994 to 2014. Urbanization was measured by economic, geographical landscape, population, and social cultural dimensions. This research suggested that urbanization generally improves hotel performance, but with different effects. Therefore, stakeholders, such as hospitality managers, could provide corresponding governance strategies according to the characteristics of the city and province in China.
Keywords: 650